Tasawuf Hamka dan Rekonstruksi Spiritualitas Manusia Modern - Sutoyo Sutoyo (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2015)
The construction of Hamka?s sufistic thought is significant for the world today, not only to reform Islamic thought but also to reconstruct modern spirituality. Modern society is now trapped by rational model and pattern of thought, discarding inner or spiritual dimension, thus resulting in a materialistic and hedonistic lifestyle. As a result, there emerges value crisis of humanity marked by the crisis of spirituality. Hamka?s sufistic thought as a form of human spiritual reconstruction is relevant to be deeply studied. This article aims to prove that spirituality constitutes human potential which is impossible to vanish in whatever situation, although human being has has arrived at the peak of rationality. Hamka?s sufistic thought is active, dynamic and progressive, emphasizing the necessity of one?s engagement in society more actively than in old sufism. Moreover, sufism has to become agent of social change from all types of life decadence. For Hamka, spirituaity is an infinite idea inherent in the totality of humanity. To deny it means to negate the selfhood of human being. Therefore, sufism is the best way to present the transcendent, because it becomes a necessity for human at the time of sorrow.